Acid/base controllable self-complexes that mimic flapping butterfly. Issue 35 (30th August 2017) - Chen, Mujuan; Liang, Jidong; Zeng, Zhijian; Lin, Xin; Zhang, Shilong; Jiang, Lasheng
Graphical abstract: Highlights: Three single-component bis-self-complexes which contain two BPP34C10 rings were presented. The bis-self-complexes will function as molecular switches under base/acid controlled. The acid/base controlled movement of bis-crown ethers mimics a flapping butterfly. Abstract: A new type of self-complexed bis-crown ether containing two bis( p -phenylene)-34-crown-10 (BPP34C10) ether rings and two secondary ammoniums has been synthesized and characterized. The formation of these bis-self-complexes has been identified by NMR spectroscopy, mass spectrometry and X-ray analysis. The acid/base controlled movement of these bis–crown ethers can mimic a flapping butterfly.